Signal Transduction-Dependent Channels - Rojas-Montecinos, P (Springer New York, 2016)
From the moment the first member of this ion channel family, Slo1, was discovered, the scientific world was confronted with a molecular Pandora’s box: once opened, its electrical language left scientists bewitched. They were fascinated with this “monster” of a single-channel conductance (250 pS in symmetrical 100 mM K+) close to the ceiling imposed by simple diffusion combined with an exquisite K+ selectivity. Slo1 channels are essentially impermeable to Na+ and conduct K+ tenfold and 200-fold more effectively than Rb+ and Cs+, respectively, though it was previously thought that large conductance channels were not supposed to be so selective. At the same time, the channel was activated by voltage and cytoplasmic Ca2+. This latter property led Meech in 1978 to hypothesize that this conductance system was perfect link between cell metabolism and electrical activity, and he was right on the mark1. Because of its large conductance, this voltage- and calcium-activated K+ channel was christened “maxi-K” or “BK” (for big K+). This high single-channel conductance is not only a characteristic of Slo1 but is shared by the other members of this family of K+ channels, Slo2 and Slo3. These channels, although similar in many aspects to the voltagegated K+ (Kv) channels, are more versatile in that their activation is modulated by ions, as is the case of Slo1. In the case of Slo2, the key modulatory ions are Na+ and Cl-ä and in Slo3, H+ (pH). © Springer Science+Business Media, LLC 2013 and Springer Science+Business Media New York 2016.